Implementasi Musrenbang Perspektif Effective Governance (Studi Kasus Musrenbang di Kecamatan Pamulang, Kota Tangerang Selatan) - Haniah Hanafie (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2016)
This paper is based on research in 2015. This study on  the implementation of  Musrenbang (Development Plan Meeting) in District Pamulang, South Tangerang City. Theory of Effective Governance and development planning, were used as a tool of analysis in this study. Previous studies used as a foothold in the study of literature. Qualitative research is an approach in this study. Interviews, review of documentation and observation used as a technique in data collection. Data were descriptive analyzed and using data processing procedures set forth McNabb (2002: 297). The results showed that, in terms of performance measurement (Callahan, 2007), South Tangerang City government seems have strategic planning yet, as a standard reference in the development implementation. Public accountability perspective (Callahan, 2007), the implementation of Musrenbang in South Tangerang City requires strict regulations and clear and strong coordination, so that at the operational level, accountability can be realized. In terms of public participation, ideally South Tangerang City Government public positioning as Voters - Local Government (administrator)  as Implementor (Callahan, 2007). Administrator has a responsibility to public by good accountability providing, showing its performance.